2015
DOI: 10.1111/are.12860
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feed processing and forms of dietary methionine on growth and IGF-1 expression in Jian carp

Abstract: In this study, a practical basal diet (control, C) was supplemented with crystal methionine (Met) (CM) or encapsulated Met (EM), and then was pelleted (P) or extruded (E) to form six diets, PC, PCM, PEM, EC, ECM and EEM. The six diets were fed to Jian carp with initial body of 8.6 AE 0.4 g for 8 weeks to evaluate the effects of Met supplementation and feed processing on growth of the fish. In pelleted diets, weight gain (WG) increased and feed conversion ratio (FCR) decreased (P < 0.05) in response to the supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…() showed that the growth and feed utilization of Pacific white shrimp were supported by MHA‐Ca supplementation when 150.0 g/kg of fish meal was replaced by soybean meal and other ingredients, at 50% and 100%. Dietary MHA‐Ca has been reported to promote the growth of hybrid striped bass ( Morone chrysops × M. saxatilis ) (Savolainen & Gatlin, ), Jian carp (Shan et al., ) and channel catfish (Zhao et al., ). The present study also showed that the supplementation of MHA‐Ca (0.1%) significantly increased WGR and reduced FCR of shrimp when compared to NC group.…”
Section: Discussionmentioning
confidence: 99%
“…() showed that the growth and feed utilization of Pacific white shrimp were supported by MHA‐Ca supplementation when 150.0 g/kg of fish meal was replaced by soybean meal and other ingredients, at 50% and 100%. Dietary MHA‐Ca has been reported to promote the growth of hybrid striped bass ( Morone chrysops × M. saxatilis ) (Savolainen & Gatlin, ), Jian carp (Shan et al., ) and channel catfish (Zhao et al., ). The present study also showed that the supplementation of MHA‐Ca (0.1%) significantly increased WGR and reduced FCR of shrimp when compared to NC group.…”
Section: Discussionmentioning
confidence: 99%
“…MHA-Ca is the combination form of calcium and MHA. Studies showed that hybrid striped bass (Savolainen & Gatlin 2010) and Jian carp (Shan et al 2015) can effectively utilize the supplemental MHA-Ca in diet. In the present study, the WG was significantly improved by the supplemental MHA-Ca, but not by the supplemental MHA when compared with the NC group, which indicated that MHA-Ca but not MHA could be effectively utilized as Met source by channel catfish.…”
Section: Discussionmentioning
confidence: 99%
“…The studies on the biological activity of MHA‐Ca were limited in aquatic animals, and the few results showed that the growth of hybrid striped bass ( Morone chrysops × M. saxatilis ) (Savolainen & Gatlin ) and Jian carp ( Cyprinus carpio var. Jian) (Shan, Li, Zheng, Zhao & Leng ) was significantly improved by the addition of MHA‐Ca. However, there is lack of information on the application of MHA‐Ca in channel catfish diet.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, long‐term feeding trial confirmed the growth‐promoting effect of dietary zinc in common carp (Ogino & Yang, 1979) through the mechanism of zinc–gene interaction and protein synthesis as suggested by Chesters (1991). Moreover, Shan et al (2017) had reported that dietary supplementation of encapsulated methionine improved the overall growth and IGF‐1 expression in Jian carp.…”
Section: Discussionmentioning
confidence: 99%